2003
DOI: 10.2320/matertrans.44.2298
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Effect on Bubble Formation at Nozzles in Liquid Aluminum

Abstract: An experimental study was undertaken to determine how wettability affect the volume and formation of gas bubble at nozzles in liquid aluminum. X-ray fluoroscope was used to carry out in-situ observation in the melt. The nozzles were made of steel, silica and alumina to establish different wettability by liquid aluminum. The frequency of bubble formation and the bubbles volume were investigated for low gas flow rate from 0.43 to 12 cm 3 /s and for various diameters of the nozzle. It was shown that bubble volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…In addition, the inlet flow rate affected size of bubble. This result agreed with findings in bubbling column [29][30][31]. The instability of inlet flow rate and high Reynolds number creates large bubbles.…”
Section: Relationship Of Carbonation and Bubblingsupporting
confidence: 92%
“…In addition, the inlet flow rate affected size of bubble. This result agreed with findings in bubbling column [29][30][31]. The instability of inlet flow rate and high Reynolds number creates large bubbles.…”
Section: Relationship Of Carbonation and Bubblingsupporting
confidence: 92%
“…This effect causes early detachment of the bubble in LBE. However, Irons and Guthrie, 13 Bai and Thomas, 14 and Gnyloskurenko and Nakamura 77 found that the average bubble sizes in liquid metal are larger than those of air bubbles in water. This may be due to the lower Bond numbers used in liquid metals compared with those in water.…”
Section: Grid Independence Test and Validationmentioning
confidence: 99%
“…This may be due to the lower Bond numbers used in liquid metals compared with those in water. It was also reported 13,14,77 that the dynamics of the bubble formation process in a liquid metal were also influenced by the presence of nonwetting or hydrophobic materials with u s > 90 0 (referred to as poor wettability). This influences the bubble base diameter along the surface material and the final detached bubble volume.…”
Section: Grid Independence Test and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the degassing technique on the quality of the aluminum alloys includes not only controlling the hydrogen content but also the resultant quality of the melt and its cleanliness. Gnyloskurenko and Nakamura 3) took advantage of in-situ observations at the melt. They found that the gas bubble volume increased as the wettability of the melt worsened, such as after using alumina nozzle.…”
Section: Introductionmentioning
confidence: 99%